Evaluasi Program Bahasa Inggris Bertujuan Khusus dengan Pendekatan CIPP - Nurhasanah Halim; Muchlas Suseno; Syamsi Setiadi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Abstract: English for Special Purposes (BIK) is English language teaching specifically designed to meet the needs of learners in an English language learning program so that they can communicate in a particular context. The qualitative study seeks to answer the research question “How far has the English Program for Special Purposes for Secretaries and Administrative Strengths been successful in meeting the English language development needs and the English learning needs of students?” by using the CIPP component in the evaluation model approach advocated by Stufflebeam. The CIPPs component is used as a guide for planning, implementation and evaluation of the ESP program through theoretical-based criteria derived from the researchers’ understanding of language learning programmes. (Kiely dan Rea-Dickins, 2005). Data collection was carried out on ten participants, two teachers and one program developer through interview techniques. The evaluation results showed that the BIK program has successfully met the language skills development needs and the English learning needs of the students. The biggest challenge in the implementation of the BIK program is to reduce the difficulty of participants in learning English without explicitly incorporating language structural elements. In addition, these evaluations also produce systematic guidelines that can be used to evaluate English for Special Purposes programmes at other program providers or can also be used in the evaluation of teaching programmes in other fields of study.